INFLUENCES OF ARCTIC OZONE HOLE ON THE STRATOSPHERIC GENERAL CIRCULATION - ヒロオカ, トシヒコ; ニシヨシ, トシヒコ; ワタナベ, シンゴ; ミヤハラ, サブロウ; HIROOKA, Toshihiko; NISHIYOSHI, Toshihiko; WATANABE, Shingo; MIYAHARA, Saburo (National Institute of Polar Research, 1999)
P(論文) Numerical experiments are performed for four years to estimate radiative and dynamical influences of the "Arctic ozone hole" on the stratospheric general circulation by using a general circulation model developed at Kyushu University. The model includes simplified ozone photochemistry interactively coupled with radiation and dynamics. The resultant temperature structure consists of cooling of about 6K in the polar lower stratosphere and warming of about 8K in the polar upper stratosphere, which intensifies the polar night jet by about 9ms^<-1>. The cooling is caused by reduction of downward motion as well as decrease of solar UV heating due to ozone depletion, while the warming is caused by dynamical heating due to enhancement of downward motion. The results imply that the feedback mechanism may strengthen the ozone hole itself. departmental bulletin paper